Challenging synthesis of bisphosphonate derivatives with reduced steric hindrance. (27th April 2021) - Chiminazzo, Andrea; Sperni, Laura; Fabris, Fabrizio; Scarso, Alessandro
Graphical abstract: Highlights: Methyl ester protected BP precursors are desirable compounds for drug development. Such BP building blocks cannot be obtained directly from dimethyl phosphite and dichloromethane. Alternative syntheses are proposed via deprotection and reprotection. The desired products were obtained in good yields. This will favorably spur the development of stereoselective reactions of BPs. Abstract: An alternative approach is reported for the synthesis of methyl ester protected bisphosphonate building blocks, such as methylene bisphosphonate, vinylidenebisphosphonate and aryl substituted prochiral vinylidenebisphosphonates, that cannot be obtained directly from dimethyl phosphite and dichloromethane.